The Effects of Curcumin on Weight Loss Among Patients With Metabolic Syndrome and Related Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Akbari, Maryam; Lankarani, Kamran B.; Tabrizi, Reza; Ghayour-Mobarhan, Majid; Peymani, Payam; Ferns, Gordon; Ghaderi, Amir; Asemi, Zatollah (Frontiers in Pharmacology, 2019)
Background and objective: The current systematic review and meta-analysis of randomized controlled trials (RCTs) was carried out to assess the influence of curcumin intake on weight among patients with metabolic syndrome and related disorders. Methods: We searched the following databases up until January 2018: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and evaluated for quality of the studies in accordance with the Cochrane risk of bias tool. Data were pooled using the inverse variance method and expressed as standardized mean difference (SMD) with 95% confidence intervals (95% CI). Results: Eighteen articles (21 studies) that comprised a total of 1,604 individuals were finally included in the meta-analysis. Curcumin intake significantly reduced body mass index (BMI) (SMD −0.37; 95% CI, −0.61, −0.13; P < 0.01), weight (SMD −0.23; 95% CI, −0.39, −0.06; P < 0.01), waist-circumference (WC) (SMD −0.25; 95% CI, −0.44, −0.05; P = 0.01), leptin levels (SMD −0.97; 95% CI, −1.18, −0.75; P < 0.001) and increased adiponectin levels (SMD 1.05; 95% CI, 0.23, 1.87; P = 0.01). We found no significant effect of curcumin intake on hip ratio (HR) (SMD −0.17; 95% CI, −0.42, 0.08; P = 0.18). Conclusions: Overall, we have found that curcumin intake among patients with metabolic syndrome and related disorders was correlated with a significant reduction in BMI, weight, WC, and leptin, and a significant increase in adiponectin levels, but did not affect HR.